Relaxation time of polypropylene glycol and polypropylene glycol dimethylether-like polymers in terms of fluid-phase temperature and pressure dependent hole fraction - YUMAK YAHŞİ, AYŞE; TAV, CUMALİ; YAHŞİ, UĞUR (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
We present a model explaining relaxation time of PPG (polypropylene glycol) and PPGM (polypropylene glycol dimethylether) as representative compounds, with different molecular weights, PPG2 (M-w = 2 kg mol(-1)), PPG3 (M-w = 3 kg mol(-1)), PPGM1 (M-w = 1 kg mol(-1)), and PPGM2 (M-w = 2 kg mol(-1)), as a function of hole fraction at various fluid phase temperatures and high pressures. Proposed model based on the structural relaxation behavior of chain molecules given by thermo-occupancy function in terms of temperature and tempetature-pressure dependent hole fraction is discussed and compared with the free volume model. The former is the most universal behavior than the latter in terms of temperature and pressure. We discuss activation energy parameter and transmission coefficient for the species in terms of chain length and end groups such as dimethylether. Scaling relaxation time parameter in the proposed model has similar trend with relaxation time parameter of Adam-Gibbs theory. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Relaxation time; Free volume; Hole fraction; Fluid-phase temperature; Simha-Somcynsky hole theory; EQUATION-OF-STATE; GLASS-FORMING LIQUIDS; STRUCTURAL RELAXATION; DIELECTRIC-RELAXATION; ALPHA-RELAXATION; VACANCY BEHAVIOR; DC-CONDUCTIVITY; DYNAMICS; TRANSPORT; LINKING